2017
DOI: 10.1108/ijopm-09-2014-0424
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between firm innovation strategy, suppliers, product innovation, and business performance

Abstract: This study uses resource dependence theory to hypothesize that a buyer's innovation strategy enhances supplier innovation focus and a buyer-supplier relationship that supports product innovation. These in turn positively impact buyer product innovation outcomes and business performance. Moreover, it is argued that the buyer-supplier relationship positively moderates the impact of supplier innovation focus on product innovation. Design/Methodology: Structural equation modeling and hierarchical linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 86 publications
3
92
0
Order By: Relevance
“…Several studies (e.g. Moreira, 2005;Jajja et al, 2017) identified that effective integration of suppliers in product development entail several benefits such as cost reduction at product development, minimisation of failure risk and time taken in product development that can lead to a competitive advantage. When natural resources are scarce, the adoption of buffering strategies (e.g.…”
Section: H4amentioning
confidence: 99%
“…Several studies (e.g. Moreira, 2005;Jajja et al, 2017) identified that effective integration of suppliers in product development entail several benefits such as cost reduction at product development, minimisation of failure risk and time taken in product development that can lead to a competitive advantage. When natural resources are scarce, the adoption of buffering strategies (e.g.…”
Section: H4amentioning
confidence: 99%
“…Product innovation scales identify the extent of the company's product innovation activities such as the improvements of existing products or services and the creation of entirely new products or services [17,23,25,34,68,69]. The high score on these scales means that the company tends to maintain a competitive advantage in the market by implementing a wider range of product innovation activities than their competitors [70][71][72][73].…”
Section: Product Innovation Intensitymentioning
confidence: 99%
“…Therefore, to clarify the boundaries of the research, this study focuses taxonomically on product versus process innovation in the context of operations management. Product innovation is illustrated as (i) a change made to the existing product or service for the benefit of customers [17,21,22] and (ii) a creation of entirely new product or service [23][24][25]. On the other hand, process innovation refers to a change in the method and knowledge that transform inputs into outputs [6,17,22,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partners can provide enhanced access to unique and valuable knowledge, which facilitates development of new products, redesigning of working practices, reconfiguring of the business models, and organizational changes. Moreover, partnering with like-minded organizations and creating conditions for effective cooperation are key drivers of innovation outcomes (Jajja, Kannan, Brah, & Hassan, 2017). Surprisingly, only a few studies have discussed the relationship between linkages and types of innovations (Durand et al, 2008;Leiponen & Helfat, 2010;Salazar et al, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%